Manufacturing custom-contoured wheelchair seating: A state-of-the-art review. (August 2019) - Nace, Susan; Tiernan, John; Ní Annaidh, Aisling
Background: Custom-contoured wheelchair seating lowers risk of pressure injury and postural deterioration while custom-contoured wheelchair seating lowers risk of pressure injury and postural deterioration while increasing the stability and functional activity of the wheelchair occupant. Producing custom-contoured seating systems has historically been a labour-intensive process custom-contoured seating systems is historically labour-intensive. Objectives: Evaluate the strengths and limitations of current manufacturing processes for custom-contoured wheelchair seating to suggest potential future manufacturing processes. Study Design: Literature review of the state of the art. Methods: Research conducted through a literature review focused on the performance of different types of custom-contoured wheelchair seating products and processes over the last 40 years. Recent literature in orthotics and prosthetics was also consulted to assess future trends in seating. Results: There are five main manufacturing processes currently used to produce custom-contoured wheelchair seating systems. No single process is yet suitable for all wheelchair users, but many manufacturers are transitioning to computer numerical controlled (CNC) milling to reduce manual labour. Adjustable micro-modular seating and moulded seat insert manufacturing are also prevalent and offer alternative seating to soft foam carving. Conclusion: There is a need in the custom wheelchair seating sector for processes that are fast, cost-effective, produce little to no material waste, and that can effectively maintain a comfortable seating micro-climate. Additive manufacturing may meet these criteria, but further evaluation is required. Clinical relevance: This review suggests that the custom-contoured wheelchair seating manufacturers are moving away from labour-intensive processes towards digital techniques, like CNC foam milling. Additive manufacturing is a potential new process that may reduce overall costs, the lead time in preparing seats and has the potential to better manage the seating micro-climate.